EVALUATION OF COSMETIC AND SATISFACTION RATE AFTER URETHROPLASTY PROCEDURE USING PPPS - Hapsari, Edhi; Wahyudi, Irfan; Rodjani, Arry (Indonesian Journal of Urology, 2012)
Objective: To evaluate patients or parents cosmetic satisfaction rate after urethroplasty procedures in patients with hypospadia. Material & Method: We prospectively collected data from parents whose children underwent urethroplasty procedures in Cipto Mangunkusumo Hospital since early 2001 until mid 2009, within 18 years old age. Data collected were age, first and last time of operation, type of hypospadia, characteristic of hypospadia, technique used for urethroplasty and time of operation. We also asked questionnaire about parental background and Pediatric Penile Perception Score (PPPS) questions, which contains (1) Satisfaction in shape and position of the urethral meatus, (2) Satisfaction in penile glans appearance, (3) Satisfaction in penile skin appearance, (4) Satisfaction in overall penile appearance. Each question has 4 types of score: very satisfied is 3, satisfied is 2, unsatisfied is 1, and very unsatisfied is 0. Using Kruskal Wallis and Mann Whitney statistical analysis, we analyzed the association between parental background, type of hypospadia, and technique used for urethroplasty with PPPS. Results: From 178 patients, 76 can be contacted. Mean age of first operation is 5,67 ± 3,66; mean PPPS for meatal appearance is 1,88 ± 0,46; mean PPPS for glans is 2,02 ± 0,32; mean PPPS for penile skin is 1,95 ± 0,39; mean PPPS for general appearance is 1,89 ± 0,45 and mean PPPS is 7,75 ± 1,31. Total PPPS based on type of hypospadia: distal hypospadia 8,1 ± 1,19; medial hypospadia 7,31 ± 1,10 and for proximal hypospadia 7,75 ± 1,32. Total PPPS based on operation technique: TIP 7,72 ± 1,17; Duckett 7,14 ± 1,35 and Onlay Island Flap 8,4 ± 1,8. Using Kruskal Wallis statistic analysis, parents satisfaction rate is significantly associated with monthly income and type of hypospadia (p